‘TAM’ in English constructions vs. Polish renditions – Selected transference pitfalls - Chłopek, Dorota (LingBaW. Linguistics Beyond and Within, 2017)
This paper argues that a cognitive, constructional, view of the English categories of tense, aspect, and mood (‘TAM’) influences comprehension resulting in a more accurate grammatical performance by Polish users of English. Five English constructions considered to be transference pitfalls for Polish users are highlighted through juxtaposing original examples from The Hobbit by Tolkien (1937/1978) with three Polish renditions. The pitfalls addressed in this paper concern absence of equivalent Polish constructions to English expressions in the perfect aspect, the progressive aspect and to English constructions which ‘lexicalize’, i.e. convey with words, a compilation of the perfect and the progressive aspects. The Polish versions of the examples analysed and discussed in the present paper demonstrate a variety of means in which Polish grammar is used to handle the disparities between the English and Polish versions. The objective of the paper is to apply a cognitive interpretation to the aforementioned English constructions.